The theory of emergency conditions is a legal way to confront the Corona pandemic - Yusuf Aziz , Header; Auda Ghanim , Prof.Dr.Yousif (Basra studies journal, 2022)
The theory of emergency conditions emerged as a legal adaptation of the Corona pandemic in order to address the fatigue in contractual obligations according to the effects of this pandemic and the subsequent administrative measures that included the general closure of various and unnecessary life facilities, and this theory witnessed recognition by the French legislator in his amendment of the Civil Code. In 2016, therefore, the research sought to clarify the position of legal legislation on this theory in light of the Corona pandemic. The study included Iraq, Egypt and France, as well as the position of the Vienna Convention and the unidroit principles of 2016 and the International Chamber of Commerce, which issued an update to the rules of the theory in 2020, and the research also sought to approach a statement regarding a general trend that adopts the principles of this theory. This is embodied in a set of judicial decisions issued by the various judicial bodies competent in this regard.